Wettability and Interfacial Phenomena Implications for Material Processing - Khanna, Rita (IntechOpen, 2019)
Wettability at the solid/liquid interface, its dynamics, tunability, the influence of operating parameters, surface and interfacial phenomena play an increasingly significant role in a wide variety of applications, for example, material processing, nanotechnology, oil recovery, oil spills, chemical leaching, water management, and disease transmission. Although a mature field, it is experiencing dramatic developments on several fronts with emerging applications in new fields. This book presents a collection of eight chapters on nanoscale wetting phenomena, oil extraction from reservoir rocks, the role of coatings, particle morphology, surface roughness and viscosity in metal processing, and practical applications of superhydrophobic behaviour in cell culturing, isolation, anti-icing, anti-reflective and anti-corrosion coatings in the transportation and optical devices fields.